ROLE OF WILD EDIBLE FRUITS USED BY THE TRIBALS FROM SHAHPUR TALUKA OF THANE DISTRICT - Mahadkar, Shivprasad D; Patil, Bhargavi Y (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were as follows: (1) The present study deals with the identification, ethno botanical exploration, and documentation of plant species that deal with wild edible fruits with respect to food and medicinal value. (2) Documentation of the medicinal value of wild edible fruits was done through discussion with local medicine men and Vaidus. Methods: The ethno botanical survey was carried out in Shahpur Taluka of Thane District from June 2021 to January 2023. The data were collected through discussions and interviews with experienced people and traditional healers. The data on wild edible fruits were collected using preparation of questionnaire in the local language and group discussions. Voucher specimens were collected during the walk with informants. The collected plants were identified using standard floras. Results: From Shahpur Taluka of Thane district, a total of 40 wild edible fruit plants belonging to 25 families have been documented. Wild edible plants play an important role in the lives of rural populations in every aspect, such as supplemented food, nutritionally balanced diets, medicine, fruits, and fodder, along with their daily income potential. Among different parts of plant species, fruits are more consumed by the tribals. Thane district is rich in indigenous plants that have been explored for their nutritional and medicinal values, and that’s why it is necessary to conserve the biodiversity, which could help to maintain and improve the source of food supply for the inhabitants. Conclusion: The present work documented 40 wild edible fruit plants. Out of these, most of the plants have medicinal value. Further investigation of their phytochemical and nutraceutical studies may provide better nutritional and medicinal sources in the future.